Peptidoglycan Hydrolases RipA and Ami1 Are Critical for Replication and Persistence of Mycobacterium tuberculosis in the Host - Claire Healy (American Society for Microbiology, 2020)
ABSTRACT Synthesis and cleavage of the cell wall polymer peptidoglycan (PG) are carefully orchestrated processes and are essential for the growth and survival of bacteria. Yet, the function and importance of many enzymes that act on PG in Mycobacterium tuberculosis remain to be elucidated. We demonstrate that the activity of the N-acetylmuramyl-l-alanine amidase Ami1 is dispensable for cell division in M. tuberculosis in vitro yet contributes to the bacterium’s ability to persist during chronic infection in mice. Furthermore, the d,l-endopeptidase RipA, a predicted essential enzyme, is dispensable for the viability of M. tuberculosis but required for efficient cell division in vitro and in vivo. Depletion of RipA sensitizes M. tuberculosis to rifampin and to cell envelope-targeting antibiotics. Ami1 helps sustain residual cell division in cells lacking RipA, but the partial redundancy provided by Ami1 is not sufficient during infection, as depletion of RipA prevents M. tuberculosis from replicating in macrophages and leads to dramatic killing of the bacteria in mice. Notably, RipA is essential for persistence of M. tuberculosis in mice, suggesting that cell division is required during chronic mouse infection. Despite the multiplicity of enzymes acting on PG with redundant functions, we have identified two PG hydrolases that are important for M. tuberculosis to replicate and persist in the host. IMPORTANCE Tuberculosis (TB) is a major global heath burden, with 1.6 million people succumbing to the disease every year. The search for new drugs to improve the current chemotherapeutic regimen is crucial to reducing this global health burden. The cell wall polymer peptidoglycan (PG) has emerged as a very successful drug target in bacterial pathogens, as many currently used antibiotics target the synthesis of this macromolecule. However, the multitude of genes encoding PG-synthesizing and PG-modifying enzymes with apparent redundant functions has hindered the identification of novel drug targets in PG synthesis in Mycobacterium tuberculosis. Here, we demonstrate that two PG-cleaving enzymes are important for virulence of M. tuberculosis. In particular, the d,l-endopeptidase RipA represents a potentially attractive drug target, as its depletion results in the clearance of M. tuberculosis from the host and renders the bacteria hypersusceptible to rifampin, a frontline TB drug, and to several cell wall-targeting antibiotics.